Osteoporosis in Healthy South Indian Males and the Influence of Life Style Factors and Vitamin D Status on Bone Mineral Density - Sahana Shetty; Nitin Kapoor; Dukhabandhu Naik; Hesarghatta Shyamasunder Asha; Suresh Prabu; Nihal Thomas; Mandalam Subramaniam Seshadri; Thomas Vizhalil Paul (Journal of Osteoporosis)
Objective. To study the prevalence of osteoporosis and vitamin D deficiency in healthy men and to explore the influence of various life style factors on bone mineral density (BMD) and also to look at number of subjects warranting treatment. Methods. Ambulatory south Indian men aged above 50 were recruited by cluster random sampling. The physical activity, risk factors in the FRAX tool, BMD, vitamin D, and PTH were assessed. The number of people needing treatment was calculated, which included subjects with osteoporosis and osteopenia with 10-year probability of major osteoporotic fracture >20 percent and hip fracture >3 percent in FRAX India. Results. A total of 252 men with a mean age of 58 years were studied. The prevalence of osteoporosis and osteopenia at any one site was 20% (50/252) and 58%, respectively. Vitamin D deficiency (<20 ng/dL) was seen in 53%. On multiple logistic regression, BMI (OR 0.3; P value = 0.04) and physical activity (OR 0.4; P value < 0.001) had protective effect on BMD. Twenty-five percent warranted treatment. Conclusions. A significantly large proportion of south Indian men had osteoporosis and vitamin D deficiency. Further interventional studies are needed to look at reduction in end points like fractures in these subjects.